Radio Suara As’adiyah Di Kabupaten Wajo (1968-2010) - Andi Fidriani Saleh; Rabihatun Idris; Patahuddin Patahuddin (Universitas Negeri Makassar, 2022)
This study aims to determine the background of the existence of Radio Voice of As'adiyah in Wajo Regency. This research is a historical research that is descriptive analytical using historical methods. The results of the study indicate that the background of the establishment of Radio Voice of As'adiyah cannot be separated from the figure of its founder, namely KH. Yunus Martan, who is sensitive to the development of science and technology, was also inspired by the religious program (MTQ) of the Province of South Sulawesi which was covered by Radio Republik Indonesia. So that in 1968 this radio officially aired with the initial goal of establishing it as a propaganda medium. For the sake of smooth management, on July 29, 1972 Radio Voice of As'adiyah was confirmed as a legal entity in the form of a Limited Liability Company (PT) with Deed Number 73 drawn up before Notary Sistke Limoa SH. at the Edge of View.